Uma investigação sobre o(s) uso(s) de calculadoras e computadores por professores de matemática da rede pública estadual de Aracaju-SE - Lima, Ivana Silva Santos (2013)
This paper shows the results of a research whose objective was to investigate how the mathematic teachers of the Statewide Network in Aracaju use the computer and calculator to approach mathematical contents. Thus initially, fourteen public schools of the state were selected, located in five geographic areas of Aracaju which have computer labs installed by ProInfo National Program of Educational Technology. From each of these schools were selected two mathematic teachers, one from elementary school and another from high school to be interviewed. Theoretical contributions of authors were adopted like Fedalto (2006), Carneiro (2008), Borba and Hairstyle (2010) and Canavarro (1993) to analyze the types of uses that teachers make of the calculator and the computer, D´Ambrosio (1989) to identify possibilities on "how" to teach Mathematics, and Lorenzato and Fiorentini (2006) for the understanding about Mathematic Education. Based on twenty-seven semistructured interviews and on the readings made it is possible to say that most teachers use the computer and calculator to teach mathematical contents, and these instruments are predominantly used as resources. Since computer use occurs in two forms, only by the teacher to expose some content or, by him and by students when after approaching the contents softwares are used to prove the theory. The main reason for this usage is due to the understanding that the computer is a tool for motivation. While the calculator is used mostly as a tool to perform calculations in order to expedite the resolution of accounts, check results, perform complex calculations accurately and less frequently it is used as a research tool.